E-COMMERCE PADA MEBEL BINTANG JAYA - Nurjani, Yeni; Lazuardi, Febrian; Mulyadi, Mulyadi (LP2M Universitas Nurdin Hamzah, 2024)
Abstract -Bintang Jaya Furniture is a business that operates in the craft industry of making furniture/furniture made from various types of very strong wood. This Bintang Jaya furniture is located in Talang Kawo Village, Bangko District, Merangin Regency, Jambi Province. Currently, the existing system at Bintang Jaya Furniture has several shortcomings, such as recording sales of furniture/furniture and reporting, which is still done manually using book records and Excel, so it experiences obstacles such as many errors in recording reports and the data produced. not correct and orders for furniture/furniture are made over the telephone. To see the report information to the leadership takes quite a long time. For this reason, researchers conducted research and looked for solutions to these problems to help, speed up and make it easier for officers to register furniture products and leaders in taking final reports and make it easier for buyers to order furniture online. Researchers used direct observation methods, interviews, and literature studies to complete the data in creating this web application. To create this application using the PHP programming language and MySQL database. The results of this research produced a web-based E-commerce application. The data that will be input is user, product, customer, order and order status data. With output, namely furniture/furniture sales reports, transaction reports, transaction reports per customer, order status reports and customer reports. This application can be developed into an Android system to increase the satisfaction of Bintang Jaya furniture customers in online services.